Pengaruh Green Innovation dan Green Process Innovation terhadap Kinerja Perusahaan - Wafiq Muwaffaq Helmi; Erna Widiastuty (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
This research aims to obtain empirical evidence on the effect of green process innovation on firm performance and provides empirical evidence that green innovation products have a positive effect on firm performance. This research conducted manufacture firm registered on Indonesia Stock Exchange (IDX) in 2016-2020. The sample in this study was obtained using a purposive sampling technique and based on predetermined criteria, a sample of 103 firm-years was obtained. The analytical method used is multiple linear analysis method with the E-views version 12. The independent variables in this study are green product innovation and green process innovation. Firm performance is the dependent variable in this study, while firm size and firm age is the control variable in this study. The results of this study indicate green product innovation have affect to firm performance at t+1 and t+2 and green process innovation has no affect to firm performance. This research contributes in terms of provide empirical evidence for researchers about the concept of green innovation and how it affects firm performance.